La volonté politique de commémoration des morts appartient aux vivants - Audrey Rousseau (Conserveries Mémorielles)
The monument materializes absence. This is a way to collectively share marks of the past revealing the political will of commemoration. Frequently referred to as the "duty of memory,” the understanding of what has been done and what can be done, do not only require observing the presence of arranged material or analyzing the intentions of the creators. It also involves taking into account cultural transmission and memory process which engage the subject-spectator to the time of interpretation. Thus to reflect on the specific context of memorials, we propose an empirical study of three "counter-monumental" works (1986 ; 1993 ; 1996) undertaken by German artist Jochen Gerz. This reflexive journey on counter-monumentalization perspectives is an invitation to pluralize the meaning of "bearing witness" to the dead and the disappeared.